Management and consequences of the rotator cuff calcific tendinopathy - (:unkn) unknown (Springer-Verlag Berlin Heidelberg, 2012)
Calcific tendinopathy of the rotator cuff represents a treatment challenge since there is no consensus on its treatment. Unfortunately, up to 38 % of the calcifications do not disappear with time. The persistence of the calcification is detrimental to the tendon biology and resistance. Thus, it is mandatory to follow up the calcification and to treat it in case it would not reabsorb spontaneously. Nonsteroidal anti-inflammatory drugs, rest, exercises, physiotherapy, and shock wave therapy are being used with varying results. Those who have not benefited from the conservative measures are indicated for nonsurgical invasive interventions or surgical treatment. Invasive interventions include steroid/anesthetic injection, barbotage (multiple needle punctures), aspiration, and ultrasound lavage. Surgical (arthroscopic) treatment should be reserved for chronic cases or for cuff ruptures due to the deposit. © 2012 ESSKA Executive Office Luxembourg Centre Médical - FNM 76, rue d'Eich 1460 Luxembourg LUXEMBOURG. All rights are reserved.